Konsep Pemberdayaan Masyarakat Menuju Ketahanan Pangan Berbasis Pertanian Ramah Lingkungan Desa Bontomanurung Kabupaten Maros - Husain; Kaslam (SOSIORELIGIUS, 2023)
This paper discusses community empowerment in building food security on an environmentally friendly basis. So far, the problems that have arisen in the community are their low awareness of the process of meeting food needs independently, unutilized unused land or seasonal land as a source of food needs and the massive use of chemical fertilizers in agricultural activities. In addition, there are several objectives in this empowerment, including finding a strategy in building and increasing food security and building public awareness to meet food needs independently. The approach used in this study is the PAR (Participatory Action Research) method, an approach that involves the community actively in understanding a problem they are facing. Empowerment carried out by an econatural society that focuses on empowering middle to lower class people, conducting environmentally friendly-based food security training starting from preparing planting media, procedures for growing food crops, the process of treating and controlling diseases in plants using natural ingredients, as well as the practice of making POC (Liquid Organic Fertilizer). Even though the changes that have been achieved through empowerment have not been fully achieved, many people are interested and have an interest in implementing them